AMF-SporeChip provides new insights into arbuscular mycorrhizal fungal asymbiotic hyphal growth dynamics at the cellular level - Richter,F; Calonne-Salmon,M; van,der Heijden MGA; Declerck,S; Stanley,CE (Lab on a Chip: miniaturisation for chemistry, physics, biology, materials science and bioengineering, 2024)
Arbuscular mycorrhizal fungi (AMF) form symbiotic associations with the majority of land plants and deliver a wide range of soil-based ecosystem services. Due to their conspicuous belowground lifestyle in a dark environment surrounded by soil particles, much is still to be learned about the influence of environmental (i.e., physical) cues on spore germination, hyphal morphogenesis and anastomosis/hyphal healing mechanisms. To fill existing gaps in AMF knowledge, we developed a new microfluidic platform – the AMF-SporeChip – to visualise the foraging behaviour of germinating Rhizophagus and Gigaspora spores and confront asymbiotic hyphae with physical obstacles. In combination with timelapse microscopy, the fungi could be examined at the cellular level and in real-time. The AMF-SporeChip allowed us to acquire movies with unprecedented visual clarity and therefore identify various exploration strategies of AMF asymbiotic hyphae. We witnessed tip-to-tip and tip-to-side hyphal anastomosis formation. Anastomosis involved directed hyphal growth in a “stop-and-go” manner, yielding visual evidence of pre-anastomosis signalling and decision-making. Remarkably, we also revealed a so-far undescribed reversible cytoplasmic retraction, including the formation of up to 8 septa upon retraction, as part of a highly dynamic space navigation, probably evolved to optimise foraging efficiency. Our findings demonstrated how AMF employ an intricate mechanism of space searching, involving reversible cytoplasmic retraction, branching and directional changes. In turn, the AMF-SporeChip is expected to open many future frontiers for AMF research.